Repolarisasi Dini Tidak Selalu Jinak - Iman Fatullah; Hauda El Rasyid (The Indonesian Heart Association, 2016)
Early repolarization (ER) pattern is marked with J-point elevation, slurring or notching the terminal portion of the QRS and ST segment elevation has been considered benign over the last few decades. However, some reports now suggest a link between early repolarization and increased risk of death due to arrhythmias and idiopathic ventricular fibrillation (VF), known as ER syndrome. Implantable cardioverter-defibrillators implantation and drug isoproterenol are the suggested therapy in patients with ER syndrome. In contrast, patients without symptoms of the syndrome ER are common and have a better prognosis. Risk stratification in asymptomatic patients in the ER remains a gray area. There are still many unanswered questions, so studies exploring the underlying mechanisms of ER continues to be developed.